The case of tradition in development of philosophical opinion (Journal of Philosophy Culture and Political Science, 2018)
This article deals with place of tradition through philosophical history in mankind’s life. Also becoming of «tradition’s» concept philosophical category and the bases of improving. World outlook of thinkers consider the tradition as an socialbinding and social-cultural base of passing of information, opinion, customs, stereotypes, algorithm through generation. It explains that custom comes from attitude of human being to the world and discipline in some situations. Philosophical meaning of custom are given. Article addresses category of «custom» and defines the meaning in philosophical history.Key words: philosophy, human, world, world outlook, custom, tradition, habit, being, value, connection.